Prevalence and Risk Factors Associated With Gestational Diabetes Mellitus Among Pregnant Women: A Cross-Sectional Study in Ghana - Boadu, Wina Ivy Ofori; Kugblenu, Philomina; Senu, Ebenezer; Opoku, Stephen; Anto, Enoch Odame (Frontiers in Clinical Diabetes and Healthcare, 2022)
Gestational diabetes mellitus (GDM) is a global public health issue that have serious consequences on mother and her child’s health. However, limited data is available on the prevalence of GDM and its associated risk factors in Ghana. This study investigated the prevalence and associated risk factors of GDM among women attending selected antenatal clinics in Kumasi, Ghana. This cross-sectional study included 200 pregnant women who attended antenatal clinics from Three-selected health facilities in the Ashanti Region, Ghana. Women already diagnosed of GDM were identified through their medical records and were confirmed based on the criteria of the International Association of Diabetes and Pregnancy Study Groups (IADPSG), which uses a fasting blood glucose of ≥ 5.1 mmol/L. A well-structured questionnaire was used to collect data on socio-demographic, obstetric, clinical and lifestyle risk factors. Multivariate logistic regression models were used to determine the independent risk factors of GDM. The overall prevalence of GDM among study participants was 8.5%. GDM was prevalent among age 26 and 30 years (41.2%), married participants (94.1%) with basic education (41.2%) and being Akan by ethnicity (52.9%). Previous history of oral contraceptive use (aOR: 13.05; 95% CI: 1.43–119.23, p=0.023), previous history of preeclampsia (aOR: 19.30; 95% CI: 2.15-71.63; p=0.013) and intake of soda drinks (aOR: 10.05, 95% CI: 1.19–84.73, p=0.034) were found to be independent risk factors of GDM. The prevalence of GDM was found to be 8.5% and this was associated with the previous use of oral contraceptives, history of preeclampsia and intake of soda drinks. Public health education and dietary lifestyle modification may be required for pregnant women who are at risk of GDM.